(C2H5NH3)3[InBr6]: an indium(iii) organic–inorganic hybrid phase transition compound exhibiting a switchable dielectric response. (12th October 2021) - Zhang, Yin-Qiang; Xu, Guan-Cheng; Luo, Yan
Abstract : The organic–inorganic hybrid compound (C2 H5 NH3 )3 [InBr6 ] undergoes a phase transition at 248/253 K, and exhibits a switchable dielectric response. The phase transition is associated with the order–disorder changes of ethylammonium cations. Abstract : Organic–inorganic hybrid phase transition compounds have been receiving extraordinary interest because they have great potential in molecular dielectric switch applications. Here, an indium(iii )-based phase transition compound, (C2 H5 NH3 )3 [InBr6 ] (1 ), has been successfully synthesized. The phase transition temperature ( T c ) of 1 is 248 K in the cooling process, as certified via differential scanning calorimetry. Crystal structural analyses indicate that the phase transition is associated with the order–disorder changes of ethylammonium cations. Moreover, 1 exhibits an excellent switchable dielectric response in the vicinity of the T c . All these findings suggest that compound 1 is an excellent candidate for stimuli-responsive dielectric switchable devices.